The genus Neuroscelio Dodd (Hymenoptera: Platygastridae s.l.) reviewed: new species, distributional update, and discussion of relationships - Valerio, Alejandro A.; Masner, Lubomír; Austin, Andrew D.; Johnson, Norman F. (Zootaxa, 2009)
The genus Neuroscelio Dodd is revised and two new species are described: N. lagunai n. sp. (Australia) and N. orientalis n. sp. (Vietnam). An update to the identification key for Neuroscelio species is presented. The male of N. doddi Galloway, Masner & Austin is described, the first record of this sex for the genus. The geographic distribution of Neuroscelio is expanded to include South Australia and New South Wales in Australia, and the Oriental region. The relationships of Neuroscelio are discussed: the genus is removed from the tribe Gryonini. It does not appear to be closely related to any extant genera but is similar in several morphological aspects to the Eocene genus Brachyscelio Brues and the Cretaceous genus Cenomanoscelio Schlüter.